Behind the Scenes: The 1919 total solar eclipse and the invisible labor of the Portuguese and Brazilian observatories - Carolino, L. M.; Simões, A. (Centaurus, 2024)
This paper discusses the politics of invisibility involved in the expeditions to observe the May 29 1919 total solar eclipse, during which two British teams confirmed the light- bending prediction made by Albert Einstein: Charles R. Davidson and Andrew C. C. Crommelin in Sobral, Brazil, and Arthur S. Eddington and Edwin T. Cottingham on the African island of Príncipe, then part of the Portuguese empire. Historians have extensively discussed the different dimensions of this famous historical event, from its role in substantiating Einstein's theory of relativity to the widespread impact it had in local press around the world. Nevertheless, the success of the 1919 eclipse expeditions relied to a great extent on a network of Brazilian and Portuguese laborers who organized, managed, and made those expeditions possible, and whose work often passed unnoticed. This paper explores the sources of such an invisibility. It argues that the production of invisibility was twofold: on the one hand, it derived from Brazilian and Portuguese astronomers' own choice to eschew credit for the comprehensive logistical activities they carried out. On the other hand, the different geo-political contexts of Brazil and Portugal accounted for the visibility of Brazil vis-à-vis the invisibility of Portugal in this celebrated historical episode. By 1919, Brazil was preparing to celebrate the 100th anniversary of its independence in a phase of economic expansion, urban development, and the increasing application of techno-scientific solutions of societal problems, while Portugal was going through a very unstable political situation due to both internal and external factors, tied to the recent change of regime, World War I, and the clashes of European powers over their African colonial possessions.